Sustainable Environmental Policy: Harmonization between National Law and Local Wisdom - Andi Diza Khaerunnisa; Fitriani Syamsu Alam (Adaptive Governance Research, 2025)
Purpose: This study examines the interaction between national environmental policy and local wisdom in shaping sustainable environmental governance in Makassar, Indonesia, with particular attention to the extent of harmonization between formal regulations and culturally embedded practices. Subjects and Methods: A qualitative case study design was employed using in-depth interviews with 22 informants, participant observation, and document analysis. Data were analyzed through a thematic analysis approach involving coding, categorization, and theme development to identify recurring patterns across multiple data sources. Results: The findings reveal that local wisdom functions as an embedded governance system that regulates environmental behavior through intergenerational knowledge, moral values, and collective norms. However, the implementation of national environmental policy is constrained by bureaucratic rigidity, limited institutional capacity, and weak coordination, resulting in a mismatch between policy frameworks and local realities. Furthermore, an epistemological divide between scientific knowledge and experiential local knowledge, combined with limited community participation, creates tensions that hinder effective policy integration. Despite these challenges, partial harmonization occurs when policy initiatives align with existing local practices. Conclusions: The study concludes that sustainable environmental governance requires adaptive and integrative approaches that bridge formal policy systems and local wisdom, emphasizing participatory mechanisms, institutional flexibility, and the recognition of culturally grounded knowledge systems as essential components of governance.